(untitled) (Economics and region, 2025)
The paper examines the problems and approaches to regulating territorial processes of labour use and reproduction, organization and improvement of the employment efficiency in Ukraine. The purpose of the article is to identify problems and substantiate the priorities for regulating employment and territorial labour markets in Ukraine in the conditions of combining a range of socio-economic global, macro-regional (pan-European), and national challenges. The study relevance is determined by developing approaches to forming the systemic strategy for overcoming the martial law period consequences, modernizing, balancing the economy’s and employment territorial proportions, increasing the national enterprises and workers’ competitiveness, fulfilling Ukraine’s European integration aspirations. Among the main results: the research into the modern methodological grounds of forming and regulating the national labour market and its territorial components; the identification of deep-rooted and current problems in the functioning of Ukrainian employment sphere, industry and territorial labour markets, as well as in the activities to manage them; the definition of approaches to modernizing the territorial labour markets, the State Employment Service of Ukraine and its regional divisions, aligned with the labour and employment management principles and practices in the European macro-region developed countries; substantiation of mechanisms and strategic priorities for comprehensively solving the tasks for diversifying and balancing territorial economic systems, stimulating productive employment, improving the population labour potential, ensuring decent working conditions, preventing the qualified labour outflow from Ukraine. The study proved the significant role of increasing the efficiency of labour and employment territorial regulation mechanisms in implementing the consecutive strategy for sustainable economic, innovative and social development of Ukraine, improving the quality of the population labour potential reproduction, strengthening the national business entities and communities’ resilience.